Studies of novel perfluoroalkyl derivatives of azobenzene in solution and on surfaces - James R. Fletcher (2011)
Azobenzene based photochromics have been studied widely since the development of the first azo dye, Mauvine, by Perkin in 1856. Azo based dyes have been widely used in industry for over a century. The desire to study them arose from their ease of synthesis and the wide availability of colours which can be tuned by manipulation of the chromophores on the azo molecule itself. The ability of azobenzene to photoisomerise between trans and cis states is widely known. The change in dipole moment affords the ability to fine-tune surfaces via photoisomerisation of the azo molecule. The objective of this investigation was to alter the surface properties of a variety of substrates via the photoisomerisation reaction of several perfluoroalkyl derived azobenzene compounds. These compounds are novel and are based on the idea of the fluoroalkyl chain creating a superhydrophobic surface, similar to Teflon, which would change surface energy upon isomerisation of the azobenzene molecule to give a more hydrophilic surface. This would ultimately then be utilised to coat a fabric surface to provide a photosensitive coating. The compounds used in this work (Admat 1 and 2 and Cfam derivatives) were synthesised in order for their photochemistry in solution and on surfaces to be investigated. The studies began with the photoisomerisation investigations in solution and the calculation of the rate constant and finally the activation energies of these compounds in a variety of common solvents. Interesting results were observed in polar protic solvents which were investigated further. The discovery that aggregation occurred in polar protic solvents due to solubility issues, which in turn led to a fast rate constant was a key finding of the solution work. The surface studies began with the investigation of cellulose as a substrate due to the structural similarity it has with cotton. The azo compounds were derivatised using cyanuric chloride to afford a triazinyl group which was able to attach to the surface of the cellulose via the hydroxyl groups on the surface.